LEAN MANUFACTURING PADA PRODUKSI PRODUK TANGKI DENGAN METODE VSM DI PT. MCM - Samsudin, Samsudin; Kurniawan, IB Indra Widi; Harjiyanto, Kun; Haryudiniarti, Ayu Nurul (University of Riau Kepulauan, 2024)
PT MCM, a company that manufactures heavy equipment components, has problems in the tank manufacturing process. There are several wastes that occur, namely process time, machine and equipment layout, one of which causes the length of the process time. This study aims to analyse the production process activities and provide improvement suggestions through the Lean Manufacturing approach with detailed processes using the Operation Procces Chart. This is followed by a visual method using Value Stream Mapping. The results of the improvements made include replacing jib cranes with overhead cranes, adding work aids such as vertical lifters and permanent magnet lifters, changing the use of CO₂ gas tubes in welding from single tubes to cradles, changing the use of wire welding from rollers to wire tubes, and improving layouts to minimise the movement of the production process to be more optimal. The efficiency achieved can increase the number of tank production from 38 units to 39 units per month, improve the layout of the tank production process saving space up to 35, 81%, improve the standard time reduced to 33.33%.